A design method for layered double hydroxide steel bar rust inhibitor based on density functional theory
Through the design method based on density functional theory, the interaction between layered bimetal hydroxide and chloride ions and iron surfaces is calculated, and reinforced rust resistors with efficient capture of chloride ions and excellent rust resistance are preferred, which solves the problems of long cycles and resource waste of existing research methods, and achieves efficient rust resistor screening and research progress.
Patent Information
- Application Number
- CN202210168228.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-23
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-02-23
AI Technical Summary
The existing research methods for layered bimetallic hydroxide reinforced rust resistors have long experimental cycles, blind goals, and easy to cause waste of experimental resources, making it difficult to effectively screen samples with efficient capture of chloride ions and excellent rust resisting properties.
By using a design method based on density functional theory, by establishing a layered bimetal hydroxide supercell and iron surface supercell models, the binding energy between chloride ions, anions and layered bimetal hydroxide layer plates, and the interaction between anions and iron surfaces, a layered bimetal hydroxide reinforcement rust resistor with high efficiency in capturing chloride ions and excellent rust resistance properties are preferred.
The research cycle of layered bimetallic hydroxide reinforced bar rust resistors is shortened, experimental errors and resource waste are reduced, and the prediction accuracy of chloride ion capture ability and steel bar rust resisting properties is improved.
Smart Images

Figure BDA0003517470990000061 
Figure BDA0003517470990000062 
Figure BDA0003517470990000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of reinforced concrete structure rust inhibitors, in particular to a design method of a layered double metal hydroxide steel bar rust inhibitor based on density functional theory. Background Art
[0002] In the marine environment, chloride ion-induced steel corrosion is a common and difficult problem to solve, and a large amount of economic losses are caused by steel corrosion every year. Adding steel rust inhibitors is one of the effective ways to resist steel corrosion. Steel rust inhibitors are widely used in reinforced concrete structures due to their simple operation, low cost, and good effect. Layered double hydroxides (LDHs) have the advantages of chloride ion capture and loading anions with corrosion inhibition properties, and have great potential in the field of reinforced concrete corrosion protection. Many studies have shown that suitable layered double hydroxide steel rust inhibitors have a dual rust inhibition effect of capturing free chloride ions in the concrete environment and releasing anions with corrosion inhibition properties.
[0003] The current research process of layered double hydroxide steel bar rust inhibitor is: first try to synthesize anion intercalated layered double hydroxide steel bar rust inhibitor samples with corrosion inhibition performance, then perform phase analysis and microstructure analysis on the synthesized samples, and finally use electrochemical experiments to test the rust inhibition ability of the samples and use isothermal adsorption tests to verify their ability to capture chloride ions. The generally recognized interlayer ion exchange order is NO3 - <NO2 - <Cl - <OH - <SO4 2- ≤CO3 2- , the exchange order of a large number of organic and inorganic anions with corrosion inhibition performance has not been determined. If the synthesized layered double hydroxide cannot release anions with corrosion inhibition performance, it means that the experiment has failed. Therefore, this method of screening layered double hydroxide steel bar rust inhibitors based on a large number of experiments has a long experimental cycle, blind goals, and easily causes a waste of experimental resources, which is not conducive to promoting the research and application of layered double hydroxide steel bar rust inhibitors. Summary of the invention
[0004] In view of the above problems, the present invention proposes a design method of a layered double hydroxide steel bar rust inhibitor based on density functional theory. Starting from predicting the anion binding ability of the layered double hydroxide and the protective effect of the corrosion-inhibiting anions on the iron surface, a layered double hydroxide steel bar rust inhibitor with high efficiency in capturing chloride ions and excellent rust inhibition performance on steel bars is designed.
[0005] To achieve the above object, the technical solution adopted by the present invention is: a design method of layered double metal hydroxide steel bar rust inhibitor based on density functional theory, comprising the following steps:
[0006] S1: By establishing a layered double hydroxide supercell, the binding energy between chloride ions, anions with corrosion inhibition performance and layered double hydroxide layers was compared and analyzed based on density functional theory, and a layered double hydroxide steel bar rust inhibitor with high efficiency in capturing chloride ions was preliminarily screened out;
[0007] S2: By establishing a supercell model of the iron (100) surface or the iron (110) surface, the interaction between the anion with corrosion inhibition performance and the iron surface is calculated based on the density functional theory, and the adsorption effect of the corrosion inhibition anion on the iron surface after the corrosion inhibition anion is adsorbed is calculated. The stability of the interaction between the corrosion inhibition anion and the iron surface is verified, and the influence of the anion type on the corrosion resistance of the iron surface is compared and analyzed, and the anion with excellent rust resistance for steel bars is selected;
[0008] S3: Combining the calculation results in steps S1 and S2, a layered double metal hydroxide steel bar rust inhibitor is designed that has high efficiency in capturing chloride ions and excellent rust resistance for steel bars.
[0009] In step S1, the layered double hydroxide supercell is between 2×2×1 and 8×8×1, and the ratio of divalent metal cations to trivalent metal cations is between 2 and 8.
[0010] The layered double hydroxide steel bar rust inhibitor with high efficiency in capturing chloride ions in step S1 should satisfy the requirement that the binding energy value between the anions with corrosion inhibition performance and the layered double hydroxide layer plates is greater than the binding energy value between the chloride ions and the layered double hydroxide layer plates.
[0011] The structural optimization of the anion with corrosion inhibition performance and the layered double hydroxide supercell and the calculation of the binding energy between the anion and the layered double hydroxide layer in step S1 should use the same calculation parameters.
[0012] The anion with excellent rust-inhibiting performance in step S2 refers to an anion that has an adsorption protection effect or an oxidation protection effect on the iron surface, and the protection effect remains stable in the presence of chloride ions, that is, chloride ions cannot occupy the adsorption sites of the corrosion-inhibiting anion on the iron surface.
[0013] The iron surface in step S2 is a Fe(100) surface or a Fe(110) surface, and the supercell range of the iron surface is 3×3×1 to 6×6×1.
[0014] The same calculation parameters are used for the anion with excellent rust-inhibiting performance, the structural optimization of the iron surface, and the calculation of the interaction between the anion and the iron surface in step S2.
[0015] The layered double hydroxide steel bar rust inhibitor described in step S3, which has high efficiency in capturing chloride ions and excellent rust inhibition for steel bars, refers to a rust inhibitor that satisfies both the binding capacity of interlayer anions with the layered double hydroxide lamina less than the binding capacity of chloride ions with the layered double hydroxide lamina and the interlayer anions having a stable oxidation protection or adsorption protection on the iron surface.
[0016] The beneficial effects of the present invention are:
[0017] 1. It provides an efficient and reasonable design method for layered double metal hydroxide steel bar rust inhibitors, shortening the research cycle of layered double metal hydroxide steel bar rust inhibitors.
[0018] 2. Only quantum chemistry software is needed for modeling and calculation, which can reduce experimental errors and save a lot of experimental costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 NO3 is the NO3 of Mg2Al-NO3 LDHs steel bar rust inhibitor in Example 1 - Adsorption configurations on the Fe(100) surface, where (a) is before adsorption and (b) is after adsorption;
[0020] Figure 2 NO3 is adsorbed on the Fe(100) surface in Example 1 - The configuration of chloride ion adsorption after adsorption, where (a) is before adsorption and (b) is after adsorption;
[0021] Figure 3 NO3 is the NO3 of Mg2Al-NO3 LDHs steel bar rust inhibitor in Example 1 - Adsorption on Fe(100) surface and Fe(100) surface adsorption of NO3 - The density of states of the adsorbed chloride ions is shown below:
[0022] Figure 4 NO2 is the NO2 of Mg2Al-NO2 LDHs steel bar rust inhibitor in Example 2 - Adsorption configurations on the Fe(100) surface, where (a) is before adsorption and (b) is after adsorption;
[0023] Figure 5 The Fe(100) surface adsorbs NO2 in Example 2 - The configuration of chloride ion adsorption after adsorption, where (a) is before adsorption and (b) is after adsorption;
[0024] Figure 6 NO2 is the NO2 of Mg2Al-NO2 LDHs steel bar rust inhibitor in Example 2 - Adsorption on Fe(100) surface and Fe(100) surface adsorption of NO2- The density of states of the adsorbed chloride ions is shown below:
[0025] Figure 7 XRD diagrams of the Mg2Al-NO2 LDHs and Mg2Al-NO3 LDHs steel bar rust inhibitor samples synthesized in Examples 1 and 2;
[0026] Figure 8 The polarization resistance Rp value of each group of steel bars in the electrochemical experiment in Examples 1 and 2 changes with c(Cl - )Added change graph. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described in detail below in conjunction with the embodiments. It should be noted that the embodiments do not limit the protection scope of the present invention.
[0028] Example 1
[0029] An example of a method for designing a layered double metal hydroxide steel bar rust inhibitor based on density functional theory according to the present invention comprises the following steps:
[0030] (1) Mg4Al2(OH) 12 The CO3·3H2O primitive cell model was imported into Materials Studio software, and a 3×3×1 supercell was constructed using the Supercell button. 2- Delete and replace some Mg atoms with Al atoms so that Mg / Al=2; use CASTEP module with the following parameters: GGA-PBE functional, ultrasoft pseudopotential, cutoff energy of 340 eV, k-point value of 3×3×1; optimize NO3 in 10×10×10 cubic crystal lattice - The structure of the optimized NO3 - Uniformly placed between supercell layers. The same steps were used to construct the Mg2Al-Cl LDHs model; the binding energies of Mg2Al-NO3 LDHs and Mg2Al-Cl LDHs were calculated.
[0031] (2) The Fe unit cell model was imported into Materials Studio software to optimize the structure of the Fe unit cell. The CASTEP module was used with the following parameters: GGA-PW91 functional, ultrasoft pseudopotential, cutoff energy of 340 eV, and k-point of 4 × 4 × 1. The Fe(100) plane was cut to create 4 layers of Fe atoms and the vacuum layer, and then construct a 4×4×1 supercell, fix the bottom two layers of Fe atoms, and optimize the structure of the 4×4×1 supercell; optimize NO3 in a 10×10×10 cubic crystal lattice - The structure of the optimized NO3 -Placed in the optimized 4×4×1 supercell, calculate NO3 - Adsorption on Fe(100) surface. Chloride ions are placed in NO3 - Calculate the adsorption of chloride ions to NO3 near the adsorption site on the iron surface. - Effect of adsorption on Fe(100) surface.
[0032] (3) The anion exchange order determined by combining the binding energy values of Mg2Al-NO3 LDHs and Mg2Al-Cl LDHs, NO3 - Adsorption of NO3 on Fe(100) surface and in the presence of chloride ions - The stability of its interaction with the Fe(100) surface is analyzed to determine whether Mg2Al-NO3 LDHs is a layered double hydroxide steel bar rust inhibitor with high efficiency in capturing chloride ions and excellent rust inhibition performance for steel bars.
[0033] Synthesis of Mg2Al-NO3 LDHs steel bar rust inhibitor sample:
[0034] Mg4Al2(OH) 12 CO3·3H2O was calcined at 500℃ to obtain the calcined product LDO. 2g LDO was mixed with 200ml 0.25mol / L sodium nitrate solution and stirred for 8h at 80℃. The Mg2Al-NO3 LDHs steel bar rust inhibitor sample was obtained after filtration, washing, drying and grinding.
[0035] Electrochemical testing:
[0036] A saturated calcium hydroxide solution with a pH value of 12.5 was used as a simulated concrete pore solution. The Mg2Al-NO3 LDHs steel bar rust inhibitor sample prepared in Example 1 was added to the simulated concrete pore solution at 0.5% of the mass of the simulated concrete pore solution, and was marked as Mg2Al-NO3 LDHs. The control group B was a simulated concrete pore solution without any steel bar rust inhibitor. HPB300 steel bars with a diameter of 10 mm were cut into short steel bars with a length of 10 mm. One end face was connected with a wire, and the other end face was used as a working surface. The remaining surfaces except the working surface were sealed with epoxy resin. The working surface was polished into a mirror surface step by step with 180#-1500# aluminum oxide metallographic sandpaper. The working electrode was passivated in the simulated concrete pore solution for 8 days, and then sodium chloride was added to the sample to be tested every day to make the Cl in the sample to be tested - The concentration of Cl was increased by 0.02 mol / L every day for the first 5 days, and then by 0.01 mol / L every day. The CS235OH electrochemical workstation was used, and the test system adopted a three-electrode system: steel bar as working electrode, platinum electrode as auxiliary electrode, saturated calomel electrode as reference electrode. The self-corrosion potential of each group was tested with Cl -Changes in the graph with increasing addition concentration and electrochemical impedance spectroscopy.
[0037] Example 2
[0038] Another example of a density functional theory-based layered double hydroxide steel bar rust inhibitor design method according to the present invention comprises the following steps:
[0039] (1) Mg4Al2(OH) 12 The CO3·3H2O primitive cell model was imported into Materials Studio software, and a 3×3×1 supercell was constructed using the Supercell button. 2- Delete and replace some Mg atoms with Al atoms so that Mg / Al=2; use CASTEP module and set parameters: GGA-PBE functional, ultrasoft pseudopotential, cutoff energy of 340 eV, k-point value of 3×3×1; optimize NO2 in 10×10×10 cubic crystal lattice - The structure of the optimized NO2 - Uniformly placed between supercell layers. The same steps were used to construct the Mg2Al-Cl LDHs model; the binding energies of Mg2Al-NO2 LDHs and Mg2Al-Cl LDHs were calculated.
[0040] (2) The Fe unit cell model was imported into Materials Studio software to optimize the structure of the Fe unit cell. The CASTEP module was used to set the following parameters: GGA-PW91 functional, ultrasoft pseudopotential, cutoff energy of 340 eV, and k-point of 4 × 4 × 1. The Fe(100) plane was cut to create 4 layers of Fe atoms and the vacuum layer, and then construct a 4×4×1 supercell, fix the bottom two layers of Fe atoms, and optimize the structure of the 4×4×1 supercell; optimize NO2 in a 10×10×10 cubic crystal lattice - The structure of the optimized NO2 - Placed in the optimized 4×4×1 supercell, calculate NO2 - Adsorption on Fe(100) surface. Chloride ions are placed in NO2 - Calculate the adsorption of chloride ions to NO2 near the adsorption site on the iron surface. - Effect of adsorption on Fe(100) surface.
[0041] (3) The anion exchange order determined by combining the binding energy values of Mg2Al-NO2 LDHs and Mg2Al-Cl LDHs, NO2 - Adsorption of NO2 on Fe(100) surface and in the presence of chloride ions -The stability of its interaction with the Fe(100) surface is analyzed to determine whether Mg2Al-NO2 LDHs is a layered double hydroxide steel bar rust inhibitor with high efficiency in capturing chloride ions and excellent rust inhibition performance for steel bars.
[0042] Synthesis of Mg2Al-NO2 LDHs steel bar rust inhibitor sample:
[0043] Mg4Al2(OH) 12 CO3·3H2O was calcined at 500℃ to obtain the calcined product LDO. 2g LDO was mixed with 200ml 0.25mol / L sodium nitrite solution and stirred for 8h at 80℃. The Mg2Al-NO2 LDHs steel bar rust inhibitor sample was obtained after filtration, washing, drying and grinding.
[0044] Electrochemical testing:
[0045] A saturated calcium hydroxide solution with a pH value of 12.5 was used as a simulated concrete pore solution, and the Mg2Al-NO2 LDHs steel bar rust inhibitor sample prepared in Example 2 was added to the simulated concrete pore solution at 0.5% of the mass of the simulated concrete pore solution, marked as Mg2Al-NO2 LDHs, and the control group B was a simulated concrete pore solution without any steel bar rust inhibitor. The remaining specific test steps were the same as those in Example 1.
[0046] The results of the embodiment are as follows:
[0047] Table 1 shows the lattice constants and binding energies of Mg2Al-NO3 LDHs, Mg2Al-NO2 LDHs, and Mg2Al-Cl LDHs in Examples 1 and 2, wherein the binding energy of Mg2Al-NO3 LDHs is -45.534 eV, and the binding energy of Mg2Al-Cl LDHs is -49.965 eV; the ion exchange order Cl - >NO3 - Therefore, Mg2Al-NO3 LDHs has a high efficiency in capturing chloride ions. Figure 1 NO3 of Mg2Al-NO3 LDHs in Example 1 - Configurations before and after adsorption on Fe(100). After adsorption, N-O1 breaks and the bond length is becomes O1 moves to between Fe58 and Fe78; the Mulliken charges before and after adsorption in Table 2 show that Fe58 and Fe78 transfer a total of 0.52e outward, of which 0.36e is transferred due to adsorption with O1, and the rest is transferred to N; this indicates that the N-O1 bond is broken due to NO3 - It undergoes redox reaction with Fe(100). Figure 2 Fe(100) surface adsorbs NO3- After the adsorption of chloride ions, O1 moves from between Fe58 and Fe78 to the acupuncture point below Fe58 and Fe78; Figure 3 Compared with NO3 - Adsorbed on the Fe(100) surface, Fe(100) surface adsorbs NO3 - The state density diagram of the adsorption of chloride ions shows that the 3d orbital of Fe58 is more delocalized and the bonding range of Cl and Fe58 is wider than that of O1 and Fe58, so NO3 - It does not have a stable oxidation protection effect on the iron surface.
[0048] In summary, Mg2Al-NO3 LDHs only have efficient chloride ion capture ability.
[0049] Table 1 Lattice constants and binding energies of Mg2Al-LDHs
[0050]
[0051] Table 2 NO3 - Mulliken charge before and after adsorption on Fe(100) surface
[0052]
[0053] Table 1 shows the lattice constants and binding energies of Mg2Al-NO3 LDHs, Mg2Al-NO2 LDHs, and Mg2Al-Cl LDHs in Examples 1 and 2, wherein the binding energy of Mg2Al-NO2 LDHs is -36.534 eV, and the binding energy of Mg2Al-Cl LDHs is -49.965 eV; the ion exchange order is Cl - >NO2 - Therefore, Mg2Al-NO2 LDHs has a high efficiency in capturing chloride ions. Figure 4 is the NO2 of Mg2Al-NO2 LDHs in Example 2 - The configurations before and after adsorption on Fe(100). After adsorption, the bond lengths of N-O1 and N-O2 are becomes and The Mulliken charges before and after adsorption in Table 3 show that the charge obtained by N is 1.19e, indicating that NO2 - It undergoes a strong redox reaction with Fe(100). Figure 5 Fe(100) surface adsorbs NO2 - Then the chloride ion is adsorbed, and Cl moves from between Fe38 and Fe58 to between Fe58 and Fe78. Cl cannot occupy NO2 - Adsorption sites on the Fe(100) surface. Figure 6 NO2 - Adsorption on Fe(100) surface and Fe(100) surface adsorption of NO2 - The bonding domain of the state density diagram of the re-adsorbed chloride ion does not change, but the bonding range of the 3d orbital of Fe58 with Cl is smaller than that of the 3d orbital of Fe58 with N, so NO2 - It has a stable oxidation protection effect on the iron surface.
[0054] In summary, Mg2Al-NO2 LDHs is a layered double hydroxide steel bar rust inhibitor with high chloride ion capture ability and excellent rust inhibition performance on steel bars.
[0055] Table 3 NO2 - Mulliken charge before and after adsorption on Fe(100) surface
[0056]
[0057] Figure 7 The XRD patterns of the MgAl-LDHs samples synthesized in Examples 1 and 2 show that both MgAl-NO3 LDHs and MgAl-NO2 LDHs have characteristic peaks of hydrotalcite, indicating that the layered double hydroxide steel bar rust inhibitor was successfully synthesized. The interlayer spacings calculated from the crystal plane index 003 peak using Jade software are 0.785nm and 0.762nm, respectively, indicating that the interlayer spacing increases with the increase of ion size.
[0058] Figure 8 The polarization resistance Rp of MgAl-NO3 LDHs, MgAl-NO2 LDHs and control group B in Examples 1 and 2 changes with Cl - Concentration change trend diagram. It can be seen from the figure that with the increase of chloride ion concentration, the Rp value of the experimental group with added MgAl-NO3 LDHs and MgAl-NO2 LDHs steel bar rust inhibitors is always much greater than that of the control group B, indicating that the addition of layered double hydroxide steel bar rust inhibitors has an excellent rust inhibition effect on steel bars, and the rust inhibition effect of MgAl-NO2 LDHs is much higher than that of MgAl-NO3 LDHs, which is consistent with the calculation results based on density functional theory.
Claims
1. A design method for layered double metal hydroxide steel bar rust inhibitor based on density functional theory, characterized in that: The following steps are involved: S1: By establishing a layered double hydroxide supercell, the binding energy between chloride ions, anions with corrosion inhibition performance and layered double hydroxide layers was compared and analyzed based on density functional theory, and a layered double hydroxide steel bar rust inhibitor with high efficiency in capturing chloride ions was preliminarily screened out; The layered double metal hydroxide steel bar rust inhibitor with high efficiency in capturing chloride ions refers to a layered double metal hydroxide layer plate whose binding energy value between anions with corrosion inhibition performance and the layered double metal hydroxide layer plate is greater than the binding energy value between chloride ions and the layered double metal hydroxide layer plate; S2: By establishing a supercell model of the iron surface, the interaction between anions with corrosion inhibition performance and the iron surface is calculated based on density functional theory, and the adsorption effect of chloride ions on the iron surface after the corrosion inhibition anions are adsorbed is calculated. The stability of the interaction between the corrosion inhibition anions and the iron surface is verified, and the influence of the anion types on the corrosion resistance of the iron surface is compared and analyzed, and anions with excellent rust resistance for steel bars are selected; The anion with excellent rust-inhibiting performance refers to an anion that has an adsorption protection effect or an oxidation protection effect on the iron surface, and the protection effect remains stable in the presence of chloride ions, that is, chloride ions cannot occupy the adsorption sites of the corrosion-inhibiting anion; S3: Combining the calculation results in steps S1 and S2, a layered double metal hydroxide steel bar rust inhibitor is designed that has high efficiency in capturing chloride ions and excellent rust resistance for steel bars.
2. The design method of layered double metal hydroxide steel bar inhibitor based on density functional theory according to claim 1, characterized in that: The layered double hydroxide supercell in step S1 ranges from 2×2×1 to 8×8×1, and the ratio of divalent metal cations to trivalent metal cations ranges from 2 to 8.
3. The design method of layered double hydroxide steel bar inhibitor based on density functional theory according to claim 1, characterized in that: The same calculation parameters are used in the structural optimization of the anion with corrosion inhibition performance and the layered double hydroxide supercell and the calculation of the binding energy between the anion and the layered double hydroxide in step S1.
4. The design method of layered double metal hydroxide steel bar inhibitor based on density functional theory according to claim 1, characterized in that: The iron surface in step S2 is an Fe (100) surface or an Fe (110) surface, and the supercell range of the iron surface is 3×3×1~6×6×1.
5. The design method of layered double metal hydroxide steel bar inhibitor based on density functional theory according to claim 1, characterized in that: The same calculation parameters are used for the anion with excellent rust-inhibiting performance, the structural optimization of the iron surface, and the calculation of the interaction between the anion and the iron surface in step S2.
6. The design method of layered double metal hydroxide steel bar inhibitor based on density functional theory according to claim 1, characterized in that: The layered double hydroxide steel bar rust inhibitor described in step S3, which has high efficiency in capturing chloride ions and excellent rust resistance for steel bars, refers to a rust inhibitor that satisfies both the binding capacity of interlayer anions with the layered double hydroxide lamina less than the binding capacity of chloride ions with the layered double hydroxide lamina and the interlayer anions having a stable oxidation protection or adsorption protection on the iron surface.
Citation Information
Patent Citations
Method for improving CO2 gas adsorption performance of single-layer hydrotalcite
CN110559982A
Targeted corrosion inhibitor for marine reinforced concrete as well as preparation method and application of targeted corrosion inhibitor
CN113800553A